Addition of Different Oxygen Concentrations during Long-Term Hypothermic Machine Perfusion in a Clinically Relevant Porcine Donation after Circulatory Death Model. (July 2018) - Venema, Leonie; Brat, Aukje; Moers, Cyril; Ploeg, Rutger; Hannaert, Patrick; Minor, Thomas; Leuvenink, Henri
Abstract : N/A: COPE Consortium. Background: To date, hypothermic machine perfusion (HMP) has become standard care in many centres preserving deceased donor kidneys. Despite a significant reduction of metabolism at low temperatures, remaining cellular activity in the organ still requires oxygen. However, oxygen supply during HMP is not standard yet, as its role and safety has not been fully clarified yet. This study investigates the effect of administering oxygen during HMP on renal function in a clinically relevant porcine donation after circulatory death (DCD) model. Methods: After 30 minutes of warm ischemia, porcine slaughterhouse kidneys were preserved for 24 hours by means of static cold storage (CS), or HMP with Belzer Machine Perfusion Solution (UW- MPS) with the addition of 0%, 21% or 100% oxygen. Next, kidneys were reperfused for 4 hours in a normothermic autologous leukocyte depleted blood machine perfusion (NMP) setup. Kidneys were assessed on their renal function, oxidative stress and injury markers. Results: HMP resulted in significantly better kidney function during NMP in terms of creatinine clearance, fractional sodium excretion and proteinuria. The addition of 100% oxygen showed the highest creatinine clearance, but did not reach statistical significance. TBARS, markers of oxidative stress, were negligibly low in all preservation modalities. Urinary TBARS at the end of NMP were highest in the CS group with a mean of 11.2 μM compared to 7.7 μM in the 100% oxygen group (NS). HMP preserved kidneys showed significantly lower injury markers compared with those preserved by CS. No such differences were found between the HMP groups with different oxygen concentrations. Conclusion: This study demonstrated that kidney preservation with HMP is superior to CS. Although the addition of oxygen to HMP did not result in significantly improved renal function during NMP, beneficial effects were found in terms of reduced oxidative stress. Oxygen addition during HMP did not result in detrimental effects in this model